Strengthening cultural connectivity through integrating indigenous knowledge systems into undergraduate coursework: A perspective from Sabah. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2014)
This paper briefly discusses how traditional knowledge systems are integrated into some undergraduate coursework at Universiti Malaysia Sabah (UMS). This provides the opportunity towards strengthening cultural connectivity to indigenous communities among undergraduate students from diverse backgrounds. The challenges are examined and recommendations suggested.